INCREASING DATA TELEMETRI SOUNDING ROCKET LAPAN WITH PULSE CODE MODULATION METHODE - Arisandi , Effendi Dodi (Indonesian Journal of Aerospace, 2020)
The telemetry data of the sounding rocket when flight in the space is very important to known. This data will be used for next mission or evaluation the last rocket flight. Commonly the data of the sensor in the sounding rocket are accelerometer, gyroscope, magnetometer, GPS and so on. As much data as possible than can be sent to the ground control system when the rocket flies. The problem is when the baud rate is low so not much data can be transmitted. Another problem is when the using serial bit standard communication such as the baud rate is 115.200 which mean that the maximum data in one second is 14,400 characters. It is less than when using the PCM bit rate. Application of PCM in the telemetry for sounding rocket LAPAN is new and need development to reach the optimal. With the PCM method the communication data can transmit around 1.25Mbps or 156,250 characters based on the TR FM02-S-2 full S-band transmitter. In this research, focus to the implementation the PCM method on the FPGA for sending and receiving the data via cable. Two FPGA boards can work together for sending and receiving data with PCM method with the total bit is 1.25Mbps.